2024
DOI: 10.1093/jbi/wbad112
|View full text |Cite
|
Sign up to set email alerts
|

Breast Radiologists’ Perceptions on the Detection and Management of Invasive Lobular Carcinoma: Most Agree Imaging Beyond Mammography Is Warranted

Kristen Coffey,
Wendie A Berg,
Katerina Dodelzon
et al.

Abstract: Objective To determine breast radiologists’ confidence in detecting invasive lobular carcinoma (ILC) on mammography and the perceived need for additional imaging in screening and preoperative settings. Methods A 16-item anonymized survey was developed, and IRB exemption obtained, by the Society of Breast Imaging (SBI) Patient Care and Delivery Committee and the Lobular Breast Cancer Alliance. The survey was emailed to 2946 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A review of previous mammograms in such cases may disclose subtle and barely perceptible changes that may be compatible with the presence of smaller-size, earlier-stage ILC [16,26]. A survey among 366 radiologists, members of the Society of Breast Imaging, revealed that only 25% were confident in detecting ILC on screening mammography if the breasts were dense, and this changed to 67% in non-dense breasts; therefore, most radiologists felt that imaging beyond mammography was needed to detect ILC [27]. This is widely acknowledged even by recommendations for further imaging when the diagnosis of ILC is established, and the Hungarian National guidelines are also compatible with this [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A review of previous mammograms in such cases may disclose subtle and barely perceptible changes that may be compatible with the presence of smaller-size, earlier-stage ILC [16,26]. A survey among 366 radiologists, members of the Society of Breast Imaging, revealed that only 25% were confident in detecting ILC on screening mammography if the breasts were dense, and this changed to 67% in non-dense breasts; therefore, most radiologists felt that imaging beyond mammography was needed to detect ILC [27]. This is widely acknowledged even by recommendations for further imaging when the diagnosis of ILC is established, and the Hungarian National guidelines are also compatible with this [28,29].…”
Section: Discussionmentioning
confidence: 99%